2000
DOI: 10.1007/s004020000174
|View full text |Cite
|
Sign up to set email alerts
|

Histological and microbiological findings in non-infected and infected revision arthroplasty tissues

Abstract: An assessment of clinical and laboratory findings is generally required to distinguish between septic and aseptic loosening of a hip implant. In order to evaluate the diagnostic utility of histological and microbiological investigative techniques to differentiate between these two conditions, we analysed their results in 617 patients with hip implant loosening. Histology and microbiology study confirmed the clinical diagnosis of septic loosening in approximately 98% and 89%. respectively. The clinical diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(62 citation statements)
references
References 13 publications
2
57
0
3
Order By: Relevance
“…One of the problems associated with PJI relates to timely diagnosis of this complication [3,4]. Despite availability of various diagnostic modalities, confirmation of PJI can be difficult in some patients [19][20][21][22]. Further, there is no consensus as to what constitutes a PJI, making its diagnosis very challenging [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the problems associated with PJI relates to timely diagnosis of this complication [3,4]. Despite availability of various diagnostic modalities, confirmation of PJI can be difficult in some patients [19][20][21][22]. Further, there is no consensus as to what constitutes a PJI, making its diagnosis very challenging [23].…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is no consensus as to what constitutes a PJI, making its diagnosis very challenging [23]. Although literature abounds with reports on the accuracy of various tests for diagnosis of PJI [1,4,[20][21][22], the small sample size and the conflicting findings of studies hinder the interpretation of the available data. As screening tools ESR and CRP are excellent and they should be obtained in every patient with a painful TKA.…”
Section: Discussionmentioning
confidence: 99%
“…1,[21][22][23][24] Other studies have reported incidences of S. aureus SSI of 0.4-11.6 infections per 100 procedures for cardiothoracic procedures 1,7,[25][26][27] and 0.12-0.73 infections per 100 procedures for orthopedic procedures. [28][29][30][31] The reported incidence of postoperative S. aureus BSI after cardiothoracic procedures is 0.60-1.09 infections per 100 procedures. 1,7 Our results are generally consistent with these procedure-specific rates, although our overall rate of invasive S. aureus infection was lower than that of previously published reports.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies (11)(12)(13)(14), infection was diagnosed if at least one of the following criteria was present: growth of the same microorganism in two or more cultures of synovial fluid or periprosthetic tissue, purulence of synovial fluid or implant site, acute inflammation on histopathological examination of periprosthetic tissue, or presence of a sinus tract communicating with the prosthesis. Commonly cultured organisms are coagulase-negative staphylococcus (30%-40%), S. aureas (12%-23%), mixed flora (11%), streptococci (9%-10%), gram-negative bacilli (3%-6%), enterococci (3%-7%) and anaerobes (2%-4%) (15,16). No microorganisms are detected in about 11% of apparent infection.…”
Section: Discussionmentioning
confidence: 99%